The Effect of Temperature for Producing Thayer-Martin Agar Media Using Sheep Blood on Neisseria Gonorrhoeae Growth with Various Inoculums - Ningsih, Ika; Sumadiyo, Kayla Adyapratista (Indonesian Journal of Medical Chemistry and Bioinformatics, 2025)
Neisseria gonorrhoeae is a Gram-negative bacterium in the form of diplococci that infects mucous membranes through direct inoculation, is fastidious, and requires special media for growth because it is susceptible to heating and dryness, so it cannot survive long outside its host. Thayer-Martin agar media is a selective culture medium for the diagnosis of Neisseria gonorrhoeae bacterial infections enriched with sheep blood. The purpose of this study was to determine the optimum temperature for various temperature variations of making Thayer-Martin agar when mixing with sheep blood, compared to the temperature according to the manufacturer's procedure. Determining this ideal temperature may help improve the accuracy of the diagnosis of Neisseria gonorrhoeae infection. This study used an experimental laboratory design. Sheep blood was mixed into Thayer-Martin agar at several different temperatures: 56°C, 65°C, 75°C, and 85°C. After agar preparation, Neisseria gonorrhoeae ATCC 43069 was inoculated onto the agar with McFarland standards of 0.5, 1.0, 2.0, and 3.0. The plates were then incubated under appropriate conditions to observe bacterial growth. Neisseria gonorrhoeae showed varying growth patterns at different Thayer-Martin agar preparation temperatures, which was confirmed using ANOVA analysis with a p-value of 0.002. At 56°C, full growth was observed consistently across all McFarland turbidity standards (0.5, 1.0, 2.0, and 3.0). At 65°C, growth varied with a combination of full and half-full growth in all standards. However, temperatures of 75°C and 85°C resulted in significantly reduced growth, showing only half-full growth in all standards. Post hoc tests revealed that agar preparation at 56°C provided the most favorable conditions for Neisseria gonorrhoeae growth compared to the other temperatures tested. This study found that 56°C provided optimal conditions for the growth of Neisseria gonorrhoeae because it resulted in maximum bacterial growth. Higher temperatures, such as 65°C, 75°C, and 85°C, resulted in reduced bacterial growth, possibly due to protein denaturation or bacterial cell damage at these temperatures.